REKONSTRUKSI PERTANGGUNGJAWABAN PIDANA DALAM TINDAK PIDANA PERTANAHAN DI INDONESIA - Zulfikar Zulfikar; Rizky Ayu (Lex Lectio Law Journal, 2025)
The increasing number of criminal acts in the land sector, such as land grabbing, falsification of land documents, and abuse of authority by land officials, demonstrates systemic weaknesses in Indonesia’s land law and its enforcement, resulting in legal uncertainty and a sense of injustice for lawful land right holders. This study aims to analyze: first, the regulation and implementation of criminal liability for land-related offences in Indonesian positive law and their relevance to legal certainty; second, the factors that hinder the optimal enforcement of criminal liability in handling land crimes; and third, the ideal reconstruction of criminal liability that can more effectively ensure equitable legal certainty. The research employs a normative legal method with a descriptive-analytical character, using statute and case approaches to examine the Basic Agrarian Law, the Criminal Code/Law No. 1 of 2023, sectoral land regulations, and court decisions on land-related criminal cases. The findings reveal that although the normative basis for criminal liability and the instrument of legal certainty through land registration are formally available, their implementation is constrained by fragmented and insufficiently specific offence formulations, limited capacity and weak coordination between law enforcement agencies and land administration bodies, as well as a strong culture of informal dispute settlement that neglects effective restoration of victims’ rights. This article proposes a reconstruction of criminal liability that emphasizes the establishment of a specific category of land-related offences, strengthening the capacity and guidelines for law enforcement, and integrating criminal judgments with administrative measures and a digital land information system as prerequisites for realizing equitable legal certainty for land right holders in Indonesia.